Leveraging Cultural Heritage for Sustainable Tourism Growth: Contemporary Strategies for Conservation and Promotion - Миронов Юрій Богданович; Katyukha Denys; Yurovchyk Volodymyr; Horiunova Kateryna; Melnychenko Svitlana (Ontario International Development Agency (OIDA), 2025)
The study’s relevance is determined by the need to preserve and effectively use the national cultural heritage as a strategic resource for tourism development. Cultural heritage, which includes tangible, intangible and natural elements, is an important resource for innovative tourism development. The study aims to examine in detail the multifunctional role of cultural heritage in stimulating the development of the tourism industry, with a special emphasis on modern approaches to its preservation and promotion. The study analysed global practices of cultural heritage to increase tourist attractiveness and considered the main challenges related to preservation and economic benefits. The logical-structural method was used to create a conceptual model that explains the relationship between cultural sites and tourist demand. The use of the modal generalisation method helped to identify successful strategies for integrating heritage into tourism activities at the local and international levels. Econometric modelling allowed for a quantitative analysis of the factors influencing the demand for heritage sites. The model revealed that the parameters of tourist motivation, available time, financial capabilities and infrastructure capacities of destinations are key in shaping tourist demand. The results underline the need to develop innovative approaches to promote heritage through interactive media, educational initiatives and improved logistics. It is also important to improve infrastructure, create accessible tourism products and optimise routes to attract more tourists to cultural heritage sites.
Keywords: cultural heritage; tourism; sustainable development; econometric modelling; heritage integration; cultural promotion